Microbially induced calcite precipitation for seepage control in sandy soil - Gao, Yufeng (2021)
Microbially induced calcite precipitation (MICP) can reduce the permeability of soil by reducing the pore volumes. A MICP-based soil improvement method to control water leakage in irrigation channels and reservoirs built on sandy soil grounds is presented in this article. Using this method, a low-permeable hard crust can be formed at the soil surfaces. An experimental study was carried out to evaluate the effect of this method. Sandy soil samples were treated using four different schemes, namely, (1) surface spray, (2) surface spray with the addition of fibers, (3) surface spray and bulk stabilization, and (4) immersion stabilization. By applying around 2.6 L treatment liquid (consisting of ureolytic bacteria, 0.5 mol/L calcium chloride and 0.5 mol/L urea) to the top 2-cm thick soil, the seepage rates of the samples treated by the four different schemes could be reduced by up to 379 times. The conversion rates of calcium source in the tests were up to 89.7%. The results showed that a method of treating the soil in bulk before the formation of a crust on top of the soil layer was effective in reducing the seepage rates. After the bio-treatment, the formed low-permeable hard crust layer was 10 to 20 mm thick with a calcite content higher than 5%. Below the hard crusts, the calcite content was less than 5% and the soil was not properly cemented. Using the mercury intrusion test, it was found that both pore volumes and pore sizes of the bio-treated soil reduced significantly as compared with the untreated soil. Penetration tests using a flat-bottom penetrometer were used to assess the mechanical behavior of the bio-treated soil. The results indicated that the penetration resistance of the bio-treated soil layer was much higher than that of the untreated soil.